The first phylogenetic study of sword-tail crickets from China inferred from COI, 18S and 28S genes, with the establishment of two new genera and description of one new species (Orthoptera: Grylloidea: Trigonidiidae) - He, Zhu-Qing; Shen, Chu-Ze; Wu, Xue (Zootaxa, 2020)
The phylogenetic tree of Chinese Trigonidiinae species was reconstructed based on one mitochondrial fragment (COI) and two nuclear ribosomal loci (18S and 28S). According to the concatenated trees, we define four genus groups with high nodal supports. The subgenus Paratrigonidium should be upgraded to genus status. A new genus Abstrigonidium He gen. nov. is established and Paratrigonidium chloropodum is selected as type species (A. chloropodum comb. nov.). Amusurgus (Paranaxipha) fujianensis is moved to genus Sectus as S. fujianensis comb. nov. A new species named as Emerasoma curvicerca He gen. et sp. nov. is reported. It differs from other genera by asymmetric genitalia, and lacking stridulatory files and mirror. The type specimens are deposited in Museum of Biology, East China Normal University (ECNU).